Mechanisms of civil society to establish a culture of Waqf work - Lakhdari, Abdelhak (Journal of Human Sciences, 2022)
The aim of the research is to learn about the most important mechanisms that civil society depends on the participation in, development and revitalization of the Waqfwork, that is why the question arises about the most important of these mechanisms that adopted so that it becomes a strong culture. The study was based on a descriptive, analytical and inductive, approach. They found that the act of Waqf was essentially a community-based work and the result of a collective effort, this was reflected in the conviction of its faith and spiritual dimension and the dissemination of a culture of citizenship and contribution to local and national development, then, the mechanism of social solidarity, the encouragement of voluntary charitable work and the encouragement of community action, at the same time, the practice of State culture has become a social necessity.